Assessment of hand function using the functional dexterity test after opponensplasty in young children with Blauth type 2 hypoplastic thumb. Issue 4 (July 2020) - Iba, Kousuke; Takayama, Shinichiro; Kawabata, Hidehiko; Horii, Emiko; Kazuki, Kenichi
Abstract : The functional dexterity test (FDT) is a timed pegboard test based on the manipulation of each peg and suitable for young children as it is both simple and quick to perform. We assessed the postoperative FDT values for children with Blauth type 2 hypoplastic thumbs after opponensplasty. We evaluated hand function using FDT for 12 hands of 11 patients with Blauth type 2 hypoplastic thumbs. Opponensplasty was performed in all hands following by Huber's procedure. All patients were evaluated from 6 to 12 months after surgery for hand function using three types of FDT scores: time in seconds to complete the test (FDT time), combined total time with penalty seconds added to the initial time (FDT total), and the number of pegs per second to complete the task as a percentage against normative values (FDT speed). We compared the postoperative FDT scores with those for Blauth type 1 or 2 hypoplastic thumb patients without surgical treatment. FDT time and FDT total for the patients postoperatively were both significantly shorter than those in the type 2 patients without surgical treatment. FDT speed was significantly higher than that for the patients without surgical treatment. There were no significant differences in the three FDT scores between the postoperative patients and the type 1 patients. There were several limitations including small sample size, large ranges of the data, and high number of variables. FDT reflected postopponensplasty improvement in hand dexterity in young children with Blauth type 2 hypoplastic thumb.